FORMULASI STRATEGI PEMASARAN UNIT GRIYA TAMU PADA KOPERASI WANITA DI SURABAYA - THE, GRENOL FINSEN (Kajian Ilmiah Mahasiswa Manajemen, 2012)
This research was conducted on the services of homestay in Guest House Women Cooperation. This research purpose to find out the marketing strategy formulation Guest House Women Cooperation in Surabaya. This research used the qualitative approach, data is collected in the form of a description of the process. The data collecting techniques used in this research is the interview, observation, and the Balanced Scorecard. The Data collected in the analysis based on the strenght, weakness, opportunities, and threats (SWOT) of product, price, place, and promotion (four P’s) Guest House. The results of the analysis are obtained in the form of the creation of a special promotions every month, forming an interesting programs, increased promotional budgets that needs to be increased, establishing a good relation with consumers as well as with other companies, try to do direct marketing and public relation, and form an attractive advertising. Based on the results of the research then can suggested product strategy recommendations to make packaging products, price strategy recommendations to create a discount price based on months, place strategy recommendations to create a relationship with the Agency, and promotion strategy recommendations to create a sales promotion.